THE IMPACT OF IMPLEMENTING E-COMMERCE ON ORGANIZATIONAL PERFORMANCE - Noor Hassan Alsulaimany, Abdulaziz Almaktoom (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The implementation of e-commerce on the organization may lead to an increase in the performance of the organization and customer satisfaction. This work was therefore carried out to analyze the impact of the implementation of e-commerce in the organizational performance of a company in Saudi Arabia. This study was done based on quantitative research method. The sample population of this work were 32 employees from Global Marketing Company for Sleeping System at Saudi Arabia. In this work, the primary data were collected using survey questionnaire. The collected data were analyzed using SPSS software in terms of reliability analysis, correlation analysis and regression analysis. The key findings of this work have shown that there is no relationship between implementing the e-commerce and organizational performance. Thus, hypothesis H1 of this study is rejected. This suggests that there is an issue with the application of e-commerce to improve corporate efficiency in Saudi Arabia.